2011
DOI: 10.1097/inf.0b013e31822db54c
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Among Drug-naive and First-line Antiretroviral Treatment-failing Children in Cameroon

Abstract: HIV-1 drug resistance was low among ART-naive children and very high among those failing first-line ART. Treatment change based on GRT was successful for most children, with lopinavir/ritonavir regimens being very promising for second-line use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 66 publications
10
51
1
Order By: Relevance
“…They also found that the DNA extracted from buffy coat samples (thought to contain archived viral reservoir) demonstrated a high degree of resistant virus; however, the presence of resistance in the DNA was distributed fairly evenly between infants who did and did not experience virologic failure, which suggests that DNA analysis of infant samples after single-dose NVP was not predictive of ART success [46]. As suggested by recent studies [99], due to the cost of genotypic resistance testing, there is a need to develop in-house, cost-effective and more affordable protocols that heightened sensitivity to detect strains circulating in African populations.…”
Section: Immunological and Clinical Criteria Of The Whomentioning
confidence: 85%
See 1 more Smart Citation
“…They also found that the DNA extracted from buffy coat samples (thought to contain archived viral reservoir) demonstrated a high degree of resistant virus; however, the presence of resistance in the DNA was distributed fairly evenly between infants who did and did not experience virologic failure, which suggests that DNA analysis of infant samples after single-dose NVP was not predictive of ART success [46]. As suggested by recent studies [99], due to the cost of genotypic resistance testing, there is a need to develop in-house, cost-effective and more affordable protocols that heightened sensitivity to detect strains circulating in African populations.…”
Section: Immunological and Clinical Criteria Of The Whomentioning
confidence: 85%
“…A high prevalence of drug-resistance mutation occurs in untreated, HIV infected infants, reaching 32% in Senegal [97] and 85.4% in South Africa [98], although prevalence was much lower at 4.9% in Cameroon [99]. Longer exposure to failing regimens increased the rate of TAM, which can compromise subsequent second-line treatments [97].…”
Section: Immunological and Clinical Criteria Of The Whomentioning
confidence: 99%
“…Current treatment guidelines in the United States and Europe recommend genotypic resistance testing in all antiretroviral naive patients, including vertically infected children, to detect the presence of PDR mutations and to adapt their first-line treatment accordingly [15, 16]. Several studies have evaluated the prevalence of PDR mutations among HIV-infected children [6, 1725]; however, few have determined their effect on virological response to first-line cART [6, 14, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…For DEMG10CM008 (Genbank: JX140676), a near full-length sequence is available, which appears to be closely related throughout its length to other sequences classified as belonging to subtype G using REGA (de Oliveira et al, 2014) (data not shown). For participant 12541, a partial pol consensus sequence is available which also appears to be subtype G-like (data not shown, GenBank: JQ796143 (Fokam et al, 2011b)). Together, this suggests that the subtype G-assigned sequences in lineage G7 are not CRF06_cpx sequences that have been misclassified as subtype G. Nonetheless, CRF06_cpx env appears to be derived from a sequence related to the G env sequences of lineage G7.…”
Section: Phylogenetic Analysesmentioning
confidence: 95%